Draft Ninth Five Year Plan (1997-2002) and Annual Plan, 1997-98 Vol. II - Planning Commission (Planning Commission, 1997)
Sub-Major-head wise Outlays and Expenditure Physical Targets and Achievements A Externally Aided Projects- Outlays and Expenditure Basic Minimum Services- Outlays and Expenditure Employment
Government of Uttar Pradesh State Planning Commission
Government of Uttar Pradesh State Planning Commission